MODEL ESTIMASI BIOKINETIKA UNTUK PROSES POST-DENITRIFIKASI AIR LIMBAH DOMESTIK PADA UNIT ANAEROBIC BAFFLED REACTOR - Allen Kurniawan; Fatihaturrizky Amelia; Adhirajasa Wirayudhatama; Sulpa Yudha Prawira (JURNAL SUMBER DAYA AIR, 2021)
This study developed a combination of Continuous Stirred Tank Reactor (CSTR) for the acid fermentation and the Anaerobic Baffled Reactor (ABR) post-denitrification through high nitrite injection. Volatile Fatty Acids (VFAs) as a substrate for the post-denitrification process were optimally produced in the acid fermentation process. The aim of this study was to obtain the estimation of biokinetic values to predict the effluent wastewater quality in ABR post-denitrification process under unsteady state. The reactor was operated for HRT 7 days at temperature 25-28 ˚C and pH 6-7,2. The influent and effluent substrate concentration were monitored continuously for 160 days. Post-denitrification biokinetic from the Contois equation resulted in the value of hydrolysis rate (Kh) of 0.077 day-1, the substrate transport rate (k) of 4.364×10-6 Lmg-1day-1, maximum specific growth rate (μmax) of 0.559 day-1, half saturation constant (KS) of 0.209 mgL-1, microbial decay coefficient (b) of 0.0145 days-1; yield coefficient (Y) of 0.084 g-VSSg-COD-1. The validation of biokinetic parameters based on statistical analysis showed fairly precise results following the trend of experimental data to determine the substrate concentration in the effluent unit. Therefore, the biokinetic values can be applied in the design of ABR post-denitrification using primary sludge incorporation with high strength nitrate.Keywords:  Anaerobic baffled reactor, biokinetics, Contois, hydrolysis, post-denitrification.